Identity Negotiation: An Exploration of Racial, Cultural and Gendered Identities - Jackson, Ronald L. (Communication Quarterly)
A special issue exploring racial, cultural, and gendered identities in terms of identity negotiation is presented. Topics discussed include using cultural contacts theory to understand identity negotiation; identifying and managing identities in an interracial friendship; a genealogical exploration of negotiated racial identities in America's ethnic past; white identity in a popular children's video; collective situational ethnicity and Latino subgroup's fight for influence in American Spanish-language television; an exploration of the creative negotiation of identity in the life and music of Billie Holiday; and the imagining of individual, community, and nation in a specific example from cyberspace.